Exploring open channel block of the NMDA receptor - McClymont, David W. (2011)
The G1uN3 subunits of the NMDA receptor are thought to reduce the Ca 2+ permeability and Mg2+ sensitivity of NMDA receptors. cRNA for rat NMDA receptor subunits were injected into Xenopus oocytes and responses were recorded using two electrode voltage clamp at -100, -75 and -50 mV. G1uN1-1a/2A, GluN1-1a/2A/3A and G1uN1-1a/2A/3B containing receptors were characterised using Mgz+, memantine, philanthotoxin-343, methoctramine and MK-801. IC50 values were calculated and generally showed significant increases between those containing G1uN1-1a/2A/3 subunits and G1uN1-1a/2A, while those with G1uN3B were found to be significantly higher than G1uN3A. Activity was also typically shown to be partially restored with mutations at the N and N+1 site asparagines of G1uN3A. As the ICS0 was only partially restored the changes cannot be attributed to the loss of the N-site alone. Further differences may be due to a constricted threonine ring within the M3 vestibule region, or due to continued reduced flux through the channel. Another possibility is that to restore block it may require both the double N and N+1 mutation at the N-site. Multi-target-directed ligands combine two pharmacophores to produce drugs which retain the properties of the constituents. Memantine has been approved for use in Alzheimer's disease and there is a search for drugs that have similar actions. A range of multi-target compounds were tested to determine if NMDA receptor blockade activity was obtained. The pharmacophores explored were tacrine, donepezil, lipoic acid carvedilol and dimebon. The most promising compounds were carbacrine(3) (tacrine and carvedilol) and lipocrine (lipoic acid and tacrine), and it was found that the former was equipotent and the latter more potent than memantine. Potency was likely due to the tacrine moiety. These compounds should be further categorised to determine if they retain the kinetics that gives memantine its favourable side effect profile.